How do you find all the zeros of f(x)=x^3+x^2-11x-30f(x)=x3+x211x30?

1 Answer
Aug 12, 2016

Use Cardano's method to find Real zero:

x_1 = 1/3(-1+root(3)((-709+9sqrt(4265))/2)+root(3)((-709-9sqrt(4265))/2))x1=131+3709+942652+3709942652

and related Complex zeros.

Explanation:

color(white)()

f(x) = x^3+x^2-11x-30f(x)=x3+x211x30

color(white)()
Descriminant

The discriminant Delta of a cubic polynomial in the form ax^3+bx^2+cx+d is given by the formula:

Delta = b^2c^2-4ac^3-4b^3d-27a^2d^2+18abcd

In our example, a=1, b=1, c=-11 and d=-30, so we find:

Delta = 121+5324+120-24300+5940 = -12795

Since Delta < 0 this cubic has 1 Real zero and 2 non-Real Complex zeros, which are Complex conjugates of one another.

color(white)()
Tschirnhaus transformation

To make the task of solving the cubic simpler, we make the cubic simpler using a linear substitution known as a Tschirnhaus transformation.

0=27f(x)=27x^3+27x^2-297x-810

=(3x+1)^3-102(3x+1)-709

=t^3-102t-709

where t=(3x+1)

color(white)()
Cardano's method

We want to solve:

t^3-102t-709=0

Let t=u+v.

Then:

u^3+v^3+3(uv-34)(u+v)-709=0

Add the constraint v=34/u to eliminate the (u+v) term and get:

u^3+39304/u^3-709=0

Multiply through by u^3 and rearrange slightly to get:

(u^3)^2-709(u^3)+39304=0

Use the quadratic formula to find:

u^3=(709+-sqrt((-709)^2-4(1)(39304)))/(2*1)

=(-709+-sqrt(502681-157216))/2

=(-709+-sqrt(345465))/2

=(-709+-9sqrt(4265))/2

Since this is Real and the derivation is symmetric in u and v, we can use one of these roots for u^3 and the other for v^3 to find Real root:

t_1=root(3)((-709+9sqrt(4265))/2)+root(3)((-709-9sqrt(4265))/2)

and related Complex roots:

t_2=omega root(3)((-709+9sqrt(4265))/2)+omega^2 root(3)((-709-9sqrt(4265))/2)

t_3=omega^2 root(3)((-709+9sqrt(4265))/2)+omega root(3)((-709-9sqrt(4265))/2)

where omega=-1/2+sqrt(3)/2i is the primitive Complex cube root of 1.

Now x=1/3(-1+t). So the roots of our original cubic are:

x_1 = 1/3(-1+root(3)((-709+9sqrt(4265))/2)+root(3)((-709-9sqrt(4265))/2))

x_2 = 1/3(-1+omega root(3)((-709+9sqrt(4265))/2)+omega^2 root(3)((-709-9sqrt(4265))/2))

x_3 = 1/3(-1+omega^2 root(3)((-709+9sqrt(4265))/2)+omega root(3)((-709-9sqrt(4265))/2))